Mertein Hündsfelder: Fechtlehre mit dem Kurzen Schwert , circa 1491 AD Fight-Teaching with the Shortened Sword from Codex Speyer (137r-141r) - Szabolcs Waldmann (Bern Open Publishing, 2021)
This transcription / translation of mine was first released online in 2005 (Waldmann, 2005 and Waldmann, 2006), and in print in 2008 (Clements, 2008). Since that time we have been using these teachings extensively in our school, in the armoured classes. Together with Marcell Tóth, who is also a trainer in the same class, we have been using this translation as basis for our work; moreover, he wrote his Free Scholler paper from the very same material (Tóth, 2012). Thus, this new release of the article incorporates those seven years of practice and research.